High-performance thin-layer chromatography for the analysis of medicinal plants - Reich, Eike (Thieme, 2007)
"High-Performance Thin-Layer Chromatography for the Analysis of Medicinal Plants presents the theoretical and technical information needed to perform reliable and reproducible high-performance thin-layer chromatography (HPTLC) to establish the identity, purity, quality, and stability of raw materials, extracts, and finished botanical products." "The text provides a complete overview of the techniques and common applications of HPTLC in herbal analysis. It will help the analyst answer questions such as: Am I paying for a high-quality material, but getting a cheap adulterant? Is this raw material worth its price? Does this product comply with the claim on its label? Has the composition of this product changed after being on the shelf for mare than a year?"--Jacket.